Desarrollo de competencias docentes en el marco de la sistematización de experiencias educativas (2019)
The study of the systematization of educational experiences (SEE) is approached as a process of inquiry that subjects perform on their practices through a postgraduate training project. For this, a didactic sequence was developed with a series of activities that were validated in practice, inspired by the Model for the Development and Evaluation of Academic Competencies (M-DECA) applied to the participants of the Master's Degree in Educational Supervision of a university Venezuelan The result was the strengthening of teaching competences through the development of systematization, especially those related to supervisory management